Enforcement Titles of Labour Courts - Rijavec, Vesna (65 pravne znanosti v Mariboru, 2026)
This chapter first examines enforcement titles issued by labour courts, focusing on rulings for monetary claims in individual labour disputes and on their enforcement. Regarding the content of the operative part of a judgement, the author relies on the settled case law of the Supreme Court of the Republic of Slovenia, which dictates that courts award gross amounts. The calculation and deduction of taxes and contributions are considered public-law obligations of the employer under the Tax Law and do not fall within the scope of the judgement’s operative part because the court is not entitled to decide on taxes. When the employer avoids these duties in enforcement proceedings, the full gross amount must therefore be collected for the benefit of the employee. However, the employer’s public liability for taxes is not extinguished by the payment of the entire amount to the employee. If tax authorities subsequently enforce collection, the employer may pursue an unjust enrichment claim against the worker to recover the overpayment.